PENYELESAIAN KONFLIK DALAM NOVEL PEREMPUAN SUCI KARYA QAISRA SHAHRAZ - Novianty, Rizka Novianty; Jalil, Abdul Jalil; Rumadi, Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRAK: This study discusses about conflict resolution in the novel Perempuan Sucicreated by Qaisra Shahraz. This study also discusses about internal conflict and external conflict are found in the novel Perempuan Suci created by Qaisra Shahraz. This studyused a qualitative approachanddescriptivemethodthat aimstodescribe how internal conflict resolution and external conflict resolution in the novel Perempuan Suci created by Qaisra Shahraz. The results of the research is a classification  conflict resolution, that is internal conflict resolution and external conflict resolution in the novel Perempuan Suci created by Qaisra Shahraz. The result of  this study also  as a form documentation conflict resolution in the novel Perempuan Suci created by Qaisra Shahraz. Keywords: confllicts resolution, internal conflict, external conflict, novel Perempuan Suci